2010
DOI: 10.1021/la904619x
|View full text |Cite
|
Sign up to set email alerts
|

Critical Nuclei Size, Initial Particle Size and Packing Effect on the Phase Stability of Sol-Peptization-Gel-Derived Nanostructured Titania

Abstract: The influence of the initial particle size and packing of anatase crystallites on the phase stability of nanostructured titania was investigated. Dried anatase gels with different degrees of particle packing were prepared through the peptization-induced electrostatic stabilization of primary particles in the sol. The initial size of anatase primary particles was varied by precalcination prior to the anatase-rutile phase transformation that occurred during final calcination. In the case of well-packed titania, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 42 publications
(57 reference statements)
2
12
0
Order By: Relevance
“…After calcination at 500°C for 4 h, around 5 % of the anatase had transformed to rutile, whilst after heating at 600°C almost complete transformation of anatase to rutile had occurred. The onset of the anatase-rutile phase transition is known to be dependent on the initial particle size of the anatase crystals and also their packing density [33][34][35]. A critical anatase crystallite size of *30 nm is considered necessary for the nucleation of rutile, in good agreement with our findings (Table 3).…”
Section: Effect Of Test Conditions On the Rate Of Methylenesupporting
confidence: 90%
“…After calcination at 500°C for 4 h, around 5 % of the anatase had transformed to rutile, whilst after heating at 600°C almost complete transformation of anatase to rutile had occurred. The onset of the anatase-rutile phase transition is known to be dependent on the initial particle size of the anatase crystals and also their packing density [33][34][35]. A critical anatase crystallite size of *30 nm is considered necessary for the nucleation of rutile, in good agreement with our findings (Table 3).…”
Section: Effect Of Test Conditions On the Rate Of Methylenesupporting
confidence: 90%
“…Reported research has shown that the anatase to rutile transformation occurs at temperatures between 450 and 850 • C, depending on fabrication method and precursors [4][5][6][7][8]. Various methods such as metal dopant and morphology control have been investigated to resist the anatase-rutile transformation [9,10]. However, until now, there was little report on successfully fabricating pure anatase TiO 2 film stabilized at high temperature of over 900 • C. In order to apply anatase phase TiO 2 for various environmental applications such as gas sensors, anti-microbial sanitary wares, and self-cleaning ceramic tiles, high temperature stable anatase TiO 2 without phase transformation is essential [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Here, D is the average nanocrystalline size, K is a constant (here, a value of 1.38 was assumed (Winardi et al, 2010)), λ is the wavelength of the CuKα line (=1.5406 Å), B is the full width at half maximum which was obtained by subtracting the system value from the measured value, and θ is the peak angle. Raman spectroscopies were performed using a Horiba JY T64000 micro-Raman spectrometer (Horiba Ltd.) (excitation line was 514.5 nm).…”
Section: Methodsmentioning
confidence: 99%